The Red Blood Cell Membrane of Preterm Infants in the Early Neonatal Period - S. A. Perepelitsa; V. A. Sergunova; O. E. Gudkova (Общая реаниматология, 2014)
Objective: to study the nanostructure of red blood cell membranes and erythrocyte index in preterm neonatal infants.Subjects and methods. The trial enrolled 47 neonatal infants, including 33 preterm infants who were included in a study group and 14 fullterm infants who formed a comparative group. The gestational age of the preterm infants was 33.3±1.9 weeks and the birth weight was 2065.4±304.8 g. Red blood cell counts, hemoglobin, and erythrocyte indices were estimat ed and the red blood cells were examined using an atomicforce microscope.Results. At birth, the preterm infants showed macrocytosis, intrauterine poikylocytosis, and the impaired nanostructure of red blood cell membranes. Intrauterine hypoxia affects the red blood cell membrane nanostructures: a phospholipid bilayer and a spectrin matrix, without damaging the membrane protein component. The detected changes are reversible and directed to maintaining the functional ability of red blood cells in a critical situation. At birth, gestational age, a baby's weight, hemoglobin, and blood cholesterol and standard bicarbonate levels influence the parameters of a red blood cell component. The early neonatal period was characterized by an active process on the red blood cell membranes and a change of morphological forms, suggesting the continuing postnatal rearrangement of erythropoiesis and a preterm infant's adaptation to new environmental conditions.